If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x + 5) = 8x Reorder the terms: 2(5 + 6x) = 8x (5 * 2 + 6x * 2) = 8x (10 + 12x) = 8x Solving 10 + 12x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 10 + 12x + -8x = 8x + -8x Combine like terms: 12x + -8x = 4x 10 + 4x = 8x + -8x Combine like terms: 8x + -8x = 0 10 + 4x = 0 Add '-10' to each side of the equation. 10 + -10 + 4x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 4x = 0 + -10 4x = 0 + -10 Combine like terms: 0 + -10 = -10 4x = -10 Divide each side by '4'. x = -2.5 Simplifying x = -2.5
| (3x+4)+(2x-1)= | | 6x=2x+36 | | 9x+3x+12=0 | | 14x^2+13x+3= | | (3x+4)+(5x+2)= | | 12+(-8)= | | 5x^2+10x+20=0 | | (5x+5)+(3x-3)= | | 2(w+1)+4w=3(2w-1)+8 | | -4(v+2)+2=2(v+6) | | 5x^2=13x-12 | | 45=3x | | 60=3x+15 | | -5(a-3)=-8(a+6) | | 3x-8*17=36x | | 3x-87-7x=39+8x+6 | | -k+9+2k-6=51 | | 9y^2-30y+25=0 | | 3x-4+4=66 | | ln(7x-3)= | | ln(7x-3)=52 | | (x+2.8)(x+1.3)=0 | | 15(x^2)=0 | | 3x^4-8x^2-16=0 | | (8-5)n=43 | | -2=11+9x-15-7x | | 4k+3-3k+2=-18 | | 8+5-n=27 | | 18z-10=16z+8 | | -1.4x+3.5=0.6x+0.9 | | 0.67x-2=0.2x-0.6 | | 0.667x-2=0.2x-0.6 |